DEVELOPMENT PROSPECTSOF MANAGEMENT ACCOUNTINGIN TRADE - Olga V. Grishina (Статистика и экономика, 2016)
The article presents the methodological foundations of the study of management accounting system in the trade. The main focus is concentrated on the information component of management accounting. Сonducted of compared of management accounting with adjacent categories - financial accounting and management of trade organizations. Was developed the economic-mathematical model formation of the range of goods.